Kualitas Audit di Indonesia - Zef Arfiansyah (SUBSTANSI, 2017)
This paper studies audit quality in Indonesia. Unlike other studies, this study attempts to measure audit quality in Indonesia by using A Framework for Audit Quality issued by the International Auditing and Assurance Standards Board of the International Federation of Accountants (IFAC Framework). The data used is the result of examination to Public Accountant and KAP conducted by Financial Professional Supervisory Center of Ministry of Finance (PPPK) from 2012 until 2014.Based on the comparison between the results of examination and the IFAC Framework, it can be concluded that the audit quality in Indonesia is quite good. This is because there are 63.45% KAP in Indonesia meets the elements of audit quality tested by the PPPK.